Natriuretic peptide level at heart failure diagnosis and risk of hospitalisation and death in England 2004-2018 - Taylor, C; Lay-Flurrie, SL; Ordóñez-Mena, JM; Goyder, CR; Jones, NR; Roalfe, AK; Hobbs, FDR (BMJ Publishing Group, 2021)
Objective: Heart failure (HF) is a malignant condition requiring urgent treatment. Guidelines recommend natriuretic peptide (NP) testing in primary care to prioritise referral for specialist diagnostic assessment. We aimed to assess association of baseline NP with hospitalisation and mortality in people with newly diagnosed HF.